Proteomics of a fuzzy organelle: interphase chromatin. (17th February 2014) - Kustatscher, Georg; Hégarat, Nadia; Wills, Karen L H; Furlan, Cristina; Bukowski‐Wills, Jimi‐Carlo; Hochegger, Helfrid; Rappsilber, Juri
Synopsis <boxed-text content-type="graphic" id="embj201387614-blkfxd-0003" position="anchor" orientation="portrait"> </boxed-text> A probabilistic definition of interphase chromatin captures its dynamic and regulated composition with a new proteomics‐based quantitative protein ontology approach. This resource is subsequently applied for the identification of novel factors whose interphase chromatin association depends on cyclin‐dependent kinase (CDK). Static protein lists in organellar proteomics are replaced by degrees of chromatin involvement. Chromatin components are defined by biological co‐behavior instead of biochemical co‐purification. Interphase chromatin probabilities (ICPs) for 7635 proteins focus datasets on likely chromatin factors. Chromatin enrichment for proteomics (ChEP) defines a simple but efficient procedure to enrich chromatin for proteomic analysis. Proteomic analysis of CDK‐dependent chromatin composition reveals novel cell cycle‐regulated chromatin factors.